The Use of Cosmetic Dentistry - Daminova Marjona Iskandar qizi (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Cosmetic dentistry is a method of professional oral care that focuses on improving the appearance of your teeth. And although cosmetic dentistry procedures are usually elective rather than essential, some treatment cases also provide restorative benefits. Learn about the most common procedures and how they work.